MODEL BLENDED BERBASIS PUBLIKASI PADA MASA PANDEMI COVID- 19 - Puji Yulianty; Dede Supenti; Diah Irawati; Siti Kemalasari; Sri Dewi Hariyanti; Supriyanti Hantini; Vera Lusiana (LPPM Universitas Bina Bangsa, 2022)
This study aims to describe the application of the Blended Learning model in the fieldwork college program, so that the results of the activities and responses of students of Early Childhood Education teacher education can be seen. This research method uses a quasi-experimental design model with the equivalent time series type. The research sample was taken as many as 35 students from the Early Childhood Education Teacher Education Study Program Class of 2022 using the purposive sampling method. The results showed that the average results of field work activities at each stage always increased. Stage 1 is 75.17 (C-), stage 2 is 80.07 (B), and stage 3 is 91.17 (A-). The increase in learning outcomes is evidenced by the average n-gain value at stage 3, which is 0.83 (high criteria). The results of student responses as a whole, students feel very happy with the application of the Blended Learning model and enjoy the learning process. As many as 78% of students stated that they were interested and liked the Blended Learning model. The conclusion of the study is that students' motivation, interest, and awareness of learning increased after the Blended Learning model was applied to fieldwork activities for the Early Childhood Education Teacher Education Study Program